Educative research and pedagogy: : a political and epistemological challenge - Zoppi, Ana María (Encuentro Educativo. Revista de investigación del Instituto de Ciencias de la Educación, 2022)
I will put forward some concerns and considerations about the relationship between Pedagogy and Educational Research from my point of view as a pedagogue. The route I intend to follow will have as a kick-off my vision of what happened with Pedagogy in our history, to continue by focusing on what I consider our present political-epistemological challenge. I will suggest some focal points for the reconstruction of Pedagogy as from Educational Research, centered in the appreciation of the necessary subjects of the action, the core of possible problematization in the field, the dynamics of the theory-empirics in this context and some theoretical anchor points that guide and underpin this view. Then, I will describe, succinctly, some modalities of our praxis, as an empirical reference of what we promote. Finally, I will proclaim the right to authorization, both techno-bureaucratic and academic, as a condition to make the liberty of thought possible, without which it will fall short of sense.